Self-efficacy and Use of Digital Health Care and Social Welfare Services Among Incarcerated People: Cross-sectional Survey Study - Teemu Rantanen; Eeva Järveläinen; Teppo Leppälahti (JMIR Publications, 2022)
BackgroundThe digitization of health care and social welfare services creates many opportunities for the rehabilitation of incarcerated people and their preparation for release from prison. A range of digital platforms and technology solutions have been developed that offer multiple opportunities to handle private matters either by video conference, email, or some other digital format during imprisonment. However, incarcerated people have limited access to digital health care and social welfare services, and face challenges related to shortcomings in their digital skills and self-efficacy. ObjectiveThis article assessed the significance of incarcerated people's self-efficacy in terms of their sense of control over the use of digital health care and social welfare services. MethodsA cross-sectional study was conducted using a questionnaire. Research data were collected from 11 prisons in different parts of Finland, and a total of 225 incarcerated people responded to the survey. Statistical analyses were conducted using the Pearson product-moment correlation coefficient, 2-tailed t test, linear regression analysis, and Hayes bootstrapping method. ResultsThe results showed the significance of both general and internet-specific self-efficacy, which appear to be more important for the use of digital health care and social welfare services than factors related to a person's socioeconomic background or sentence. Age was negatively correlated with perceived control over the use of digital health care and social welfare services. Furthermore, the study emphasized the importance of support from family and friends, as well as prison employees. ConclusionsThe digitalization of prisons offers many opportunities, but special consideration should be given to how the digitization of health care and social welfare services responds to the needs of incarcerated people in terms of their integration into society and the prevention of recidivism. During imprisonment, attention should be paid to strengthening the digital skills of incarcerated people, with support provided by prison employees. In addition to providing guidance on the use of individual digital services, the study recommends strengthening the general digital skills of incarcerated people, as well as developing their life management skills.